Delaying Ice and Frost Formation Using Phase‐Switching Liquids. Issue 17 (15th March 2019) - Chatterjee, Rukmava; Beysens, Daniel; Anand, Sushant
Abstract: Preventing water droplets from transitioning to ice is advantageous for numerous applications. It is demonstrated that the use of certain phase‐change materials, which are in liquid state under ambient conditions and have melting point higher than the freezing point of water, referred herein as phase‐switching liquids (PSLs), can impede condensation–frosting lasting up to 300 and 15 times longer in bulk and surface infused state, respectively, compared to conventional surfaces under identical environmental conditions. The freezing delay is primarily a consequence of the release of trapped latent heat due to condensation, but is also affected by the solidified PSL surface morphology and its miscibility in water. Regardless of surface chemistry, PSL‐infused textured surfaces exhibit low droplet adhesion when operated below the corresponding melting point of the solidified PSLs, engendering ice and frost repellency even on hydrophilic substrates. Additionally, solidified PSL surfaces display varying degrees of optical transparency, can repel a variety of liquids, and self‐heal upon physical damage. Abstract : Certain phase‐change materials can significantly delay icing and frosting in bulk form or, being infused into hydrophilic textured substrates, exhibit varying degrees of optical transparency, can repel a myriad of liquids thereby preventing staining, are capable of self‐repairing by being resilient toward mechanical damage during condensation, and thus can have far‐reaching technological impact.